Rezolvati problema:
-1+5•[(-4-2)•(-5)-17]-(+18-10)•(+7)
Răspunsuri la întrebare
Răspuns de
4
-1 +5*[-6 * (-5)-17] -8 *7=
=-1 +5 * (30-17)-56=
=-1 +5*13 -56
= -57 +65
=8
=-1 +5 * (30-17)-56=
=-1 +5*13 -56
= -57 +65
=8
Răspuns de
0
-1+5•[(-4-2)•(-5)-17]-(+18-10)•(+7)=
4*[-6*(-5)-17]-8*7=
4*(30-17)-56=
4*13-56=
52-56=-4
4*[-6*(-5)-17]-8*7=
4*(30-17)-56=
4*13-56=
52-56=-4
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă